Oxygen levels in controlled atmosphere storage of carabao mangoes (Mangifera indica L. var. Carabao) - Angeles, Aurora Aguas; De Leon, Sonia Y. (1967)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mango -- Storage